Functional diversity is a passenger but not driver of drought‐related plant diversity losses in annual grasslands. (19th August 2019) - Miller, Jesse E. D.; Li, Daijiang; LaForgia, Marina; Harrison, Susan
Abstract: Effects of climate change on plant community functional diversity are of interest since experiments have found functional diversity to predict ecosystem function. Functional diversity has been hypothesized to confer resilience to plant communities (as a "driver" of community change), but in unmanipulated natural communities, it might alternatively (or additionally) act as a "passenger" by responding to changes in plant diversity caused by extrinsic factors such as climate. We examined trends in plant functional diversity in annual grasslands in Northern California over a 19‐year period, during which a trend towards drier winters had previously been associated with the losses of drought‐intolerant species. We tested whether functional diversity decreased over the period of the study (acting as a passenger), and also whether initial site functional diversity influenced the degree of community change over the study period (acting as a driver). Initial community functional diversity was not related to species richness loss or community variability. We found that functional diversity declined as plant species richness and community mean specific leaf area declined over the course of the study, and all of these trends were associated with declining precipitation, indicating that functional diversity acted as a passenger of community change. Synthesis . This study is among the first to demonstrate that recent climatic trends may drive loss of functional diversity. Our findings highlight that functional diversity does not necessarily confer community resilience when its variation is shaped by the environment rather than by experimental treatments. Abstract : This study is among the first to demonstrate that recent climatic trends may drive loss of functional diversity. Our findings highlight that functional diversity does not necessarily confer community resilience when its variation is shaped by the environment rather than by experimental treatments.